Ecologies of green finance: Green Sukuk and development of green Infrastructure in Bekasi Regency on SWOT Analysis - Mohammad Hatta Fahamsyah; Afif Mustafid Taftazani; Adrianna Syariefur Rakhmat; Muhammad Hamdan Ainul Yaqin (Institute of Computer Science (IOCS), 2023)
As a crucial player in promoting well-being, the Indonesian government has a vital role in fostering economic growth and infrastructure development in different cities of Indonesia. However, a significant challenge faced by the country involves striking a balance between infrastructure development and environmental conservation, in line with the principles of sustainable development goals. To tackle this issue, this study utilized a qualitative descriptive approach, focusing on the case of Bekasi Regency in West Java. Data for the research was collected through interviews with officials from the Bekasi Regency Government, as well as through document analysis and literature review. The analysis primarily revolved around a SWOT analysis. The research findings indicate that Bekasi Regency possesses favorable geographical advantages, regulations, and legal frameworks that enable the issuance of sukuk (Islamic bonds) and support green infrastructure development through financing from green sukuk. However, the current situation reveals a lack of green infrastructure development in Bekasi Regency financed by sukuk or green sukuk. Most of the existing green infrastructure projects in the city are initiated by various ministries rather than being led by Bekasi Regency itself.